Initial immune reaction and angiogenesis in bone healing. (11th April 2012) - Schmidt‐Bleek, Katharina; Schell, Hanna; Lienau, Jasmin; Schulz, Norma; Hoff, Paula; Pfaff, Michael; Schmidt, Gregor; Martin, Claudia; Perka, Carsten; Buttgereit, Frank; Volk, Hans‐Dieter; Duda, Georg
Abstract During hematoma formation following injury, an inflammatory reaction ensues as an initial step in the healing process. As granulation tissue matures, revascularization is a prerequisite for successful healing. The hypothesis of this study was that scarless tissue reconstitution in the regenerative bone healing process is dependent on a balanced immune reaction that initiates revasculatory steps. To test this hypothesis, cellular composition and expression profiles of a bone hematoma (regenerative, scarless) was compared with a muscle soft tissue hematoma (healing with a scar) in a sheep model. Upregulation of regulatory T helper cells and anti‐inflammatory cytokine expression (IL‐10) coincided with an upregulation of angiogenic factors (HIF1α and HIF1α regulated genes) in the regenerative bone hematoma but not in the soft tissue hematoma. These results indicate that the timely termination of inflammation and early onset of revascularization are interdependent and essential for a regenerative healing process. Prolonged pro‐inflammatory signaling occurring in a delayed bone‐healing model supports the finding that timely termination of inflammation furthers the regenerative process. Differing cellular compositions are due to different cell sources invading the hematoma, determining the ensuing cytokine expression profile and thus paving the path for regenerative healing in bone or the formation of scar tissue in muscle injury. Copyright © 2012 John Wiley & Sons, Ltd.